Resilient Coastal Communities of Bontang Kuala: The Role of Digital Communication Strategy in Post-Crisis Recovery - Ibrizah, Ziya; Nurrohman, Rosyid; Sarifuddin, Andri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study explores the role of digital communication strategies in strengthening the resilience and post-crisis recovery of coastal communities, with a specific focus on Bontang Kuala, a floating settlement in East Kalimantan, Indonesia. Employing a qualitative descriptive approach and a case study design, the research examines how localized digital practices support socio-economic adaptation in a vulnerable coastal setting. Data were collected through semi-structured interviews, observation, and secondary sources, then analyzed thematically using NVivo. Findings reveal that digital platforms particularly WhatsApp, Facebook, and Instagram have become crucial tools for coordination, economic revitalization, and social solidarity during recovery periods. Community-led digital initiatives, such as online tourism campaigns and crowdfunding, demonstrated the potential of digital media to enhance collective action and restore livelihoods. However, digital inequality persists due to uneven access, literacy gaps, and connectivity limitations, particularly among older fishermen and women entrepreneurs. The study concludes that digital communication functions not merely as a technological solution but as a social mechanism fostering collaborative resilience and adaptive learning. The results offer theoretical contributions to digital resilience communication and practical implications for inclusive digital transformation policies in coastal regions.